Atorvastatin influence on cardiac function and rhythm variability in patients with chronic lymphocytic leukemia in remission - B. B. Samura (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Purpose – to evaluate atorvastatin influence on cardiac hemodynamics and rhythm variability in patients with chronic lymphocytic leukemia (CLL) in remission.